Studies on Growth and Various Properties of Triglycine Sulfate (TGS) Crystals Doped with Copper Sulphate - P. Selvarajan, K. Balasubramanian (Recent Research in Science and Technology, 2010)
Pure and copper sulpahte-doped Triglycine Sulfate(TGS) salts were synthesized and single crystals of the synthesized salts were grown from aqueous solutions by slow evaporation technique. The structural studies on the grown crystals were carried out by single crystal XRD analysis and found that the grown crystals crystallize in monoclinic structure. The FTIR spectra have been recorded in the range 500-4000 cm-1 and the functional groups of the grown crystals have been identified. UV-Visible spectra show that the grown crystals have wide optical transparency in the entire visible region. Atomic absorption study reveals the presence of copper in the doped TGS crystals. Density of the samples have been measured by floatation method. The dielectric studies for the pure and copper sulphate-doped TGS crystals have been performed by measuring the dielectric parameters like dielectric constant and dielectric loss at a constant frequency of 1000 Hz with the temperatures ranging from 30 to 75 oC and this study reveals an increase of dielectric constant and loss when TGS crystal is doped with copper sulphate. Microhardness studies have been carried out to analyse the mechanical strength of the samples.